Establishing zebrafish as a model to study the anxiolytic effects of scopolamine. Issue 1 (December 2017) - Hamilton, Trevor; Morrill, Adam; Lucas, Kayla; Gallup, Joshua; Harris, Megan; Healey, Meghan; Pitman, Taylor; Schalomon, Melike; Digweed, Shannon; Tresguerres, Martin
Abstract Scopolamine (hyoscine) is a muscarinic acetylcholine receptor antagonist that has traditionally been used to treat motion sickness in humans. However, studies investigating depressed and bipolar populations have found that scopolamine is also effective at reducing depression and anxiety symptoms. The potential anxiety-reducing (anxiolytic) effects of scopolamine could have great clinical implications for humans; however, rats and mice administered scopolamine showed increased anxiety in standard behavioural tests. This is in direct contrast to findings in humans, and complicates studies to elucidate the specific mechanisms of scopolamine action. The aim of this study was to assess the suitability of zebrafish as a model system to test anxiety-like compounds using scopolamine. Similar to humans, scopolamine acted as an anxiolytic in individual behavioural tests (novel approach test and novel tank diving test). The anxiolytic effect of scopolamine was dose dependent and biphasic, reaching maximum effect at 800 µM. Scopolamine (800 µM) also had an anxiolytic effect in a group behavioural test, as it significantly decreased their tendency to shoal. These results establish zebrafish as a model organism for studying the anxiolytic effects of scopolamine, its mechanisms of action and side effects.